Wacana dan Kontroversi Ajaran Tasawuf Syekh Abdul Hamid Abulung di Kota Kandangan - Noor Ainah (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
The discourse and controversy about understanding and practicing the teachings of sufism is indeed not a new phenomenon in Indonesia, but in the Kandangan, precisely in the village of Mandapai is something new. There is a small community emerged that was different from usual in understanding and practicing the teachings of sufism taught by Sheikh Abdul Hamid Abulung or Datu Abulung. The research problem is the discourse of the teachings of sufism taught by Sheikh Abdul Hamid Abulung and the controversy of Sufism teachings of Sheikh Abdul Hamid in the city of Kandangan. The type of research used is field research and also the approach used is a qualitative approach. The data collection techniques used interviews, observations, and documentations. The findings in the field are based on interviews with the tomb guard as well as his descendants that among the teachings delivered by Datu Abulung, the essence of prayer is actually dhikr. Prayers are done not only to make Allah swt happy, but to dhikr (remember) Allah swt. and prevent the seeds of fahsya' and evil deeds. Understanding like this has an impact on the need to do daim prayers. While the teachings of sufism Shaykh Abdul Hamid Abulung are understood by a small number of controversial people, namely remembering Allah without the other practices.